Efficient synthesis of gamma-keto sulfones by NHC-catalyzed intermolecular stetter reaction - Bhunia, Anup; Yetra, Santhivardhana Reddy; Bhojgude, Sachin Suresh; Biju, Akkattu T. (Organic Letters, 2012)
The N-heterocyclic carbene-catalyzed intermolecular Stetter reaction of aldehydes with α,β-unsaturated sulfones allows the atom-economic and selective formation of γ-keto sulfones in good yields. Key to the success of this unique transition-metal-free carbon–carbon bond-forming reaction is the right choice of the NHC precursor and base. The reaction tolerates a broad range of different aldehydes.